2023
DOI: 10.1002/alz.13415
|View full text |Cite
|
Sign up to set email alerts
|

Symptom‐led staging for semantic and non‐fluent/agrammatic variants of primary progressive aphasia

Chris J. D. Hardy,
Cathleen Taylor‐Rubin,
Beatrice Taylor
et al.

Abstract: INTRODUCTIONHere we set out to create a symptom‐led staging system for the canonical semantic and non‐fluent/agrammatic variants of primary progressive aphasia (PPA), which present unique diagnostic and management challenges not well captured by functional scales developed for Alzheimer's disease and other dementias.METHODSAn international PPA caregiver cohort was surveyed on symptom development under six provisional clinical stages and feedback was analyzed using a mixed‐methods sequential explanatory design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Following previously described methods [8], two of the authors (including non-verbal thinking and personality, B1; and personal care and wellbeing, B2). Qualitative input on these symptoms was gathered from members of the UK national PPA Support Group [10], via an online survey hosted on the Opinio platform.…”
Section: Exploratory Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Following previously described methods [8], two of the authors (including non-verbal thinking and personality, B1; and personal care and wellbeing, B2). Qualitative input on these symptoms was gathered from members of the UK national PPA Support Group [10], via an online survey hosted on the Opinio platform.…”
Section: Exploratory Surveymentioning
confidence: 99%
“…Language and communication functions are not comprehensively captured by standard clinical rating scales developed for typical AD [7]. It has recently been shown that symptom-based staging informed by lived experience is feasible for other primary progressive aphasia (PPA) syndromes [8]; however, a similar tool to signpost the evolution of communication problems is lacking for lvPPA. This is particularly urgent with the advent of disease-modifying therapies for AD, as the eligibility of individuals with lvPPA and other forms of 'atypical' AD remains unclear [9] and may be confounded by misleadingly poor performance on standard, language-weighted cognitive tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Additionally, given the heterogeneity of PPA, a COS should include consideration of the value of different outcomes for different PPA syndromes. 19 We have no roadmap at present for determining or evaluating intervention outcomes in PPA and it presents radically different challenges to stroke aphasia (the current standard for aphasia interventions)-both due to its intrinsically progressive nature and also because it entails significant issues with non-verbal cognition and behaviour over the course of the illness that interacts with communication functionthus, there is a fundamental need to reorient researchers and clinicians to PPA. [18][19][20] In summary, there is a need for a specific COS, that details key measures addressing the needs of people with PPA.…”
Section: Open Accessmentioning
confidence: 99%
“…PPA causes important changes in functional communication (FC), which is defined as the "transactional success" of expression [6], and which is a fundamental feature of human connection [7]. FC ability in PPA diverges by variant, individual differences, and time [5,[8][9][10]. A person-centered approach-a holistic and humanistic method that promotes the autonomy and needs of the patient-is integral to establish how individual differences can impact a person's success in FC [9,11] and to deliver individualized care [9,12].…”
Section: Introductionmentioning
confidence: 99%